Identificación de causas que inciden sobre la calidad del agua de la Quebrada Tobales, Duitama (2023)
The Los Tobales stream, source of supply for the rural aqueduct in Vereda Florida in the Duitama Municipality, is susceptible to polluting agents, which can significantly affect the physicochemical and microbiological characteristics of the water. Identifying and evaluating the impacts that affect the quality of the water in the creek through physical-chemical and microbiological analysis, will allow establishing a pattern of the current conditions of the creek, in terms of water quality before and after its treatment. In addition, it will promote the necessary actions to prevent, mitigate, correct the effects of these impacts that modify its state, with the aim of making it suitable for human consumption. It was possible to demonstrate after the analyzes carried out that the quality of the water of the Tobales stream is not suitable for human consumption and once treated, it does not comply with the parameters established by Resolution 2115 of 2007 in terms of its quality for consumption.